(untitled) - Pinkerton, William J. (New York,London, 2003)
This title presents the keys to making every project a bottom-line success - from start to finish! In business, every brilliant idea must first answer a simple question before approval or implementation: How will it impact the bottom line? That's why if overseeing capital improvement projects from conception to completion is part of your work, "Project Management: Achieving Project Bottom-Line Succe
Keywords: Project management,Quản lý dự án